Grain refinement by rapid cyclic heating and its effect on cleavage fracture behaviour of an S690 high strength steel - V. Bertolo; L. Vilasi; Q. Jiang; T. Riemslag; S. Scott; C.L. Walters; J. Sietsma; V. Popovich (Journal of Materials Research and Technology, 2023)
The simultaneous improvement of strength and toughness with grain refinement is widely known. However, the literature lacks studies on the grain refinement effect on cleavage fracture toughness in multiphase steels containing detrimental brittle inclusions. Understanding whether the grain refinement can effectively improve fracture toughness of such steels will allow for the improvement of their design. Therefore, a quenched and tempered S690QL high strength steel with Nb-rich and oxide inclusions was subjected to a rapid cyclic heating (RCH) treatment aimed at grain refinement, followed by quenching and tempering to produce a microstructure equivalent to the as-received steel. The microstructure was investigated via scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and electron backscatter diffraction (EBSD). The cleavage fracture toughness was measured via three-point bending tests at −100 °C. The RCH effectively reduced the prior austenite grain size by 55%. However, other microstructural changes occurred. The elongated, parallel-aligned block sub-structure of martensitic/bainitic grains changed to rounded, randomly distributed blocks. Also, the ferritic content increased and martensite and cementite clusters were formed. The concurrent effects of microstructural modifications and grain refinement explain the very minor improvements in hardness and tensile properties. The grain refinement, theoretically responsible for decreasing the ductile-to-brittle transition temperature, improved the fracture toughness up to a factor of 2.5 and 8.6 when Nb-rich and oxide inclusions trigger fracture, respectively. The microstructural changes have minor effects on fracture toughness. Therefore, the proposed RCH treatment is effective in reducing the grain size and improving cleavage fracture toughness in steels containing brittle inclusions.